KIDPRENEUR AN EARLY EFFORT OF PLANTING ENTREPRENEURSHIP IN CHILDREN TO EMBRACE THE FUTURE - Bowo, Prasetyo Ari (Indonesian Journal of Early Childhood Education Studies, 2013)
Population growth measured geometrically will difficult to be matched by the growth of employment opportunities that grow arithmetically. There are plenty economic factors that cause it. To meet their needs often as a challenge filled with looking for a good job and high income.Indonesia with large population only has small number entrepreneur, according the report, the number of entrepreneur in Indonesia less than one percent, meanwhile the ideal number for a country is eight percent. This circumstance still far away from seven percent of averageneighboring countries. Increasing number of entrepreneur will accelerate economic so that people can reduce dependency to job opportunity. Kidpreneur from the beginning to the children about self-employment to prepare them better when they are as adults to meet these economic challenges. Thus, the entrepreneurial is not only as an alternative but as a freedom in life to determine the way of managing their finance.